O corpo, a dança e os territórios da Congada: um estudo sobre a expressão corporal como ato de resistência negra em Ituiutaba - MG - Neves, João Paulo Miros (2023)
Ituiutaba, in the state do Minas Gerais, at the Triângulo Mineiro region, city in which occurs the Congada celebration since 1951. The theme of this research is the Congada celebration seeing the body language as a way of anti-racist resistance. The main goal of our work is to comprehend the body as a way of resistance and black identity in the cultural, social, and geographical space of the Congada celebration taking place in the city of Ituiutaba. To reach this goal, we divided it in four specific goals: comprehend the body as a subject of study of the Social Sciences, particulary the Geography; understand the Congada celebration from the geographical point of view; analyse the body language that is part of the Congada celebration, and analyze the dance as a tool to fight racism in an action to create territories that allow black people to manifest their authenticity. We propose the following questions to guide our work: In which way the body is studied as a subject of research in the human sciences, particularly the Geography? In which ways are the bodies of the people of color are repressed and marginalized socially in Brazil? How the body can be used as a toll of social fight against these ways of repression and marginalization? By what means the dance represent a way of resistance in the Congada celebration in the city of Ituiutaba. From the theoretical point of view, our work consists in a study of the Cultural Geography of critical basis, grounded in a qualitative study, having as a perspective the study of the body. The methodology of the work was divided in three parts, whereas in the first part we did a literary revision of the main concepts of the work, and the documentary research of the data sources. The second part of the methodology consisted in the observation of the Congada celebration and the photographic coverage of the event, as well as interviews with the Congada group captains and photographic records of the headquarters of each group. The third and final part consisted in analyzing the data gathered using the photographic records and footage, as well as the combination of the bibliographic data, and the documents and the interviews, so that, by interpreting all the information, the final text could be written. As a result, we have the comprehension that the celebration, despite maintaining the memories and traditions from the times of slavery, and also from the African continent, has elements of white washing and cultural appropriation in its practices, but these elements have been fought by the new generations of Congada dancers, who proposes themselves to question and reinvent the past. When analyzing the bodily expressions present in the Congada Celebration, we have observed that they constitute a powerful form of resistance and a manifestation of black identity, reaffirming Afro-Brazilian culture and challenging the forms of oppression and social marginalization faced by non-white bodies in Brazil. Dance plays a fundamental role in this resistance, serving as a tool to combat racism. Through dance, the Congada dancers express their authenticity, claim their space, and challenge negative stereotypes associated with African culture. Our findings underscore the need to promote racial equity and combat the structural racism prevalent in our society. Finally, the research highlights the relevance of studying the body in the social sciences, particularly in Cultural Geography, as an approach that enables us to understand the interactions between culture, space, and identity.